(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2026)
Bricks are an essential material in construction, but the production has considerable environmental and health impacts. Consequently, ecobricks have emerged as a potential sustainable alternative to conventional bricks. These environmentally friendly substitutes are made by filling recycled polyethylene terephthalate (PET) plastic bottles with compacted plastic waste to a specific density. In this study, the optimum density of plastic waste in PET bottles was optimised to produce ecobricks with suitable strength properties. This innovation aimed to use plastic bottles as a building material and offers a sustainable alternative for the construction industry. Seven samples with a density of 0 g/mL to 0.65 g/mL were empirically tested for compressive strength, impact resistance, flexural strength, and failure behaviour. The findings revealed that Sample E exhibited the best performance compared to other samples. This sample achieved a compressive strength of 17.54 N/mm2, demonstrating strong structural performance. In the drop test (1 m, 2 m, and 3 m), Sample E also showed no visible denting, with a measured density (0.45 g/mL) exceeding 0.33 g/mL. It also recorded flexural strengths of 4.65 N/mm2 at the neck, 6.59 N/mm2 at the body and 11.96 N/mm2 at the bottom. These results not only exceed the minimum compressive strength for bricks (5.2 N/mm2) required by the Malaysian Public Works Department but also fulfil the Global Ecobrick Alliance guideline for minimum density (0.33 g/mL) of an ecobrick. In summary, this study helps to reduce the amount of plastic disposed of in landfills by reusing plastic waste as functional building materials. Most importantly, these findings support the United Nations Sustainable Development Goals (SDGs), specifically SDG 9 (Industry, Innovation and Infrastructure) by promoting the sustainable development of infrastructure through innovative materials and SDG 13 (Climate Action) by reducing the impact on the environment through the reduction of plastic waste.